Modernization of Public Transportation in Semarang: Transition and Challenges, 2009-2017 - Octavian Yodya Pratama; Putri Agus Wijayati (Universitas Hamzanwadi, 2026)
Bus Rapid Transit (BRT) in Semarang City was introduced to the public in 2009. At the beginning of its operation, this bus received sharp criticism regarding chaos and system unpreparedness. However, after various improvements were made, BRT transformed into a new face of public transportation and a solution to the traffic congestion problems faced by Semarang City. This study uses a historical method supported by primary sources obtained from newspapers. The results reveal that the presence of BRT, followed by the emergence of online transportation, has successfully shifted the face of public transportation, which was previously dominated by city transportation (angkot) and city buses. In addition, the transition in public transportation has impacted the lives of workers in the transportation sector who face the challenges of modernization and technological revolution.